2018
DOI: 10.1177/1744806918754612
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of toll-like receptor 4 alleviates hyperalgesia induced by acute dural inflammation in experimental migraine

Abstract: ObjectiveAlthough nociceptive sensitisation is an important pathophysiological process in migraine and migraine chronification, its underlying mechanisms remain unclear. Toll-like receptor 4 (TLR4), a pattern-recognition molecule, has a critical role in both neuropathic pain and morphine tolerance. The present study examined whether elements of the TLR4 pathway contribute to hyperalgesia induced by dural inflammation in rats.MethodsA rat model of migraine was established by infusing a dural inflammatory soup. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…Inflammatory mechanism can be involved in pathogenesis of migraine patients, showed by our study due to the increased CRP in both study groups compared with control group. Other studies also demonstrated the contribution of inflammatory mechanism in migraine pathophysiology, neurogenic inflammation being one of the most important mechanism involved in this disease [19,20]. Smoking was also an important contributing factor to migraine pathophysiology as our result demonstrated, being demonstrated as an factor which enhance oxidative stress [21].…”
Section: Discussionsupporting
confidence: 78%
“…Inflammatory mechanism can be involved in pathogenesis of migraine patients, showed by our study due to the increased CRP in both study groups compared with control group. Other studies also demonstrated the contribution of inflammatory mechanism in migraine pathophysiology, neurogenic inflammation being one of the most important mechanism involved in this disease [19,20]. Smoking was also an important contributing factor to migraine pathophysiology as our result demonstrated, being demonstrated as an factor which enhance oxidative stress [21].…”
Section: Discussionsupporting
confidence: 78%
“…Toll-like receptor 4 (TLR4) plays a crucial role in the innate immunity, and is expressed in microglia [19,20] . A previous study reported that TLR4 had a critical role in experimental migraine [21] . Intriguingly, Miyoshi and co-workers found that nerve injury induced the expression of IL-18 in spinal microglia through TLR4/p38MAPK pathway [11] .…”
Section: Discussionmentioning
confidence: 96%
“…Glial cells were activated in the status of experimental migraine, and subsequently released various proinflammatory cytokines like IL-1β and TNF-α, causing hyperpathia or allodynia [2,21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study revealed the TLR4-NF-κB signaling pathway an important role in the progress of hyperalgesia following IS dural infusions [21] . In this work, IS dural infusions induced an increase of NF-κB phosphorylation in the medullary dorsal horn (Fig.…”
Section: Microglia-derived Il-18 Mediated Astrocytic Activation Via Amentioning
confidence: 98%